9 A rapid protocol for aspirin desensitisation following hypersensitivity reactions: our single-centre experience in patients with stable and unstable coronary artery disease. (June 2018) - Jackson, Matthew; Callaghan, Sarah; Austin, David; Muir, Douglas; Sutton, Andrew; Wright, Robert; Williams, Paul; Hall, Jim; Carter, Justin; Belder, Mark de; Swanson, Neil
Abstract : There are limited data on aspirin desensitisation for patients with coronary disease. 1 This study aimed to evaluate our single-centre experience with a rapid oral desensitisation regime in patients with aspirin sensitivity undergoing coronary angiography. Methods: This single-centre retrospective observational study includes patients with self-reported hypersensitivity reactions to aspirin confirmed by clinical history who were planned to undergo coronary angiography with intent to perform percutaneous coronary intervention between Jan 2012 and Jan 2017. The aspirin desensitisation protocol is shown in table 1. All patients had blood pressure, oxygen saturation and peak flow measurements every 30 min during the dug administration and for 3 three hours after the final dose. Continuous ECG monitoring was not routinely performed unless clinically indicated. No patients received pre-treatment with steroids, antihistamines or antileukotrienes. The primary outcome was cessation of aspirin due to recurrent hypersensitivity reaction within 12 months. Results: Twenty-four patients were included in the study including patients with both stable coronary disease (7 cases) and acute coronary syndromes (NSTEMI (8 cases), STEMI (9 cases)). Previous reactions reported were mucocutaneous reactions in 17 patients (urticaria in 3 (13%), non-urticarial rash in 6 (25%), angio-oedema in 8 (33%)), respiratory sensitivity in 4 patients (17%) and systemic anaphylactoid reactions in 3 patients (13%). Percutaneous coronary intervention (PCI) was performed in 17 patients (71%) and coronary artery bypass grafting in 1 patient (4.2%). Desensitisation was acutely successful in 22 patients (92%). Two cases were unsuccessful, both following primary PCI (previous true anaphylactoid reaction experienced bronchospasm requiring nebulised salbutamol (1 case), previous angio-oedema experienced an exacerbation of her poorly controlled asthma (but no angio-oedema) treated with nebulised salbutamol (1 case)). Both patients were discharged on single antiplatelet therapy (clopidogrel and prasugrel respectively). Fifteen successfully desensitised patients completed 12 months of aspirin; no patients suffered a recurrent hypersensitivity reaction. Aspirin was stopped prior to 12 months in seven patients (replaced by formal anticoagulation (1 case), no antiplatelet or only single antiplatelet clinically indicated and clopidogrel chosen (4 cases), patient choice without evidence of recurrent hypersensitivity (1 case), death due to cardiogenic shock following STEMI (1 case)). Conclusion: Our rapid desensitisation protocol is significantly faster than the ADAPTED registry protocol (120 vs 330 min) and appears as effective across a wide range of clinical presentations and hypersensitivity reactions. Reference: . Rossini R, et al. Results of the Multicenter ADAPTED Registry (Aspirin Desensitization in Patients with Coronary Artery Disease). Circ Cardiovasc Interv. 2017;10:e004368.